Pengembangan Sistem Informasi Manajemen Pengelolaan Masjid Raden Patah Universitas Brawijaya berbasis Web - Mikail Afghan Baihaqy; Nurudin Santoso; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mosque is a place for worship activities. Not only a place for prayer, but in the past mosque was as a study center. With the development of mosques in various of campuses in Indonesia, Masjid Raden Patah, which is the main University of Brawijaya mosque, is one of the best in terms of carrying out various types of activities, activities and routine coaching programs. However, in managing various activities at the Masjid Raden Patah, most of them are still managed by one person who is the Managerial in Takmir Masjid Raden Patah. Management activities that include routine activities such as prayer schedules, routine study schedules, routine coaching schedules, and incidental events are required to publish information with several social media including live streaming, generate mosque calendar activities so that they can be easily recognized by all University academics in University of Brawijaya. System for managing activities and publishing information is important even though technically the Masjid Raden Patah already has a website address and various kinds of social media but still needs additional features to help manage all mosque activities, so not only for publication but also manage activities at the same time. Therefore Masjid Raden Patah need a management information system, that is Web-Based Masjid Raden Patah University of Brawijaya Management Information System, built using the Rapid Application Development (RAD) method in developing software to get 100% when all test scenarios are carried out, and in compatibility testing this system can works without problems in 75% of the 11 browsers tested.